2016
DOI: 10.15671/hjbc.20164417526
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Antimicrobial Activity of Pyocyanin Produced by Pseudomonas aeruginosa Strains Isolated from Different Clinical Specimens

Abstract: Ö Z E T P seudomonas aeruginosa suşları tarafından üretilen piyosiyanin karakteristik mavi-yeşil bir fenazin pigmentidir. Çalışmanın amacı, P. aeruginosa suşlarında en yüksek piyosiyanin üretiminin belirlenmesi ve piyosiyaninin Escherichia coli, Bacillus sp., Pseudomonas aeruginosa, Candida sp. and Aspergillus niger üzerindeki antimiktobiyal etkisinin araştırılmasıdır. Bu doğrultuda, piyosiyanin P. aeruginosa kültür süpernatanından özütlendi ve saflaştırıldı, ardından spektrofotometrik olarak ölçüldü. En yükse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
1
10
1
Order By: Relevance
“…Abdul-Hussein & Atia 34 reported that the growth of Escherichia coli and of Aspergillus fumigatus were inhibited in the range between 10 to 100 μg ml −1 , while the growth of yeast Cryptococcus neoformans was equally inhibited by pyocyanin. In another study, E. coli, Bacillus sp., and Aspergillus niger strains were found to be sensitive to the phenazin pigment pyocyanin at 0.005 to 50 µg as analyzed by the tube dilution and agar well diffusion methods 35 . The antagonistic activity of pyocyanin was studied at low concentration of 100 µL against Macrophomina phaseolina plant pathogenic fungus that is responsible for stem rot, seedling blight and root rot.…”
Section: Discussionmentioning
confidence: 99%
“…Abdul-Hussein & Atia 34 reported that the growth of Escherichia coli and of Aspergillus fumigatus were inhibited in the range between 10 to 100 μg ml −1 , while the growth of yeast Cryptococcus neoformans was equally inhibited by pyocyanin. In another study, E. coli, Bacillus sp., and Aspergillus niger strains were found to be sensitive to the phenazin pigment pyocyanin at 0.005 to 50 µg as analyzed by the tube dilution and agar well diffusion methods 35 . The antagonistic activity of pyocyanin was studied at low concentration of 100 µL against Macrophomina phaseolina plant pathogenic fungus that is responsible for stem rot, seedling blight and root rot.…”
Section: Discussionmentioning
confidence: 99%
“…The siderophore pyoverdine was isolated from P. aeruginosa 25W using a previously reported method ( Özyürek et al, 2016 ). Briefly, the bacterial seed culture was grown in an Luria-Bertani (LB) medium for a period of 12 h. The actively growing seed culture (O.D.…”
Section: Methodsmentioning
confidence: 99%
“…Pyoverdine and cyclodipeptides are prominent examples from Pseudomonas aeruginosa and help bacteria to chelate iron and facilitate quorum sensing ( Visca et al, 2007 ). Additionally, P. aeruginosa synthesizes water diffusible, blue-green colored pigment, pyocyanin, which shows antibacterial properties ( Crosa and Walsh, 2002 ; Özyürek et al, 2016 ). In this work we demonstrated rapid, synthesis of anisotropic gold and silver PNPs using pyoverdine and pyocyanin obtained from an indigenously isolated strain of P. aeruginosa ( Mavrodi et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…The two greatest potential perspectives for the use of pyocyanin are in industry or in pharmacology, given its antimicrobial nature. The bioprospecting of pyocyanin is based on the fact that the pigment is an active redox compound, i.e., an extracellular electron carrier agent, with NADH as the initial endogenous and molecular reducer [ 107 , 128 ]. Microbial fuel cells (MFC) are devices that convert metabolic energy into electrical current using P. aeruginosa or other bacteria [ 170 ].…”
Section: Pyocyanin Applications and Perspectivesmentioning
confidence: 99%